KLRB1 expression in nasopharyngeal mucosa as a prognostic biomarker in COVID-19 patients - Marilina García-Aranda; María Ángeles Onieva; Desirée Martín-García; Raúl Quirós; Inmaculada López; María Padilla-Ruiz; Teresa Téllez; Beatriz Martínez-Gálvez; María Luisa Hortas; Alberto García-Galindo; José González-Gomariz; Rubén Armañanzas; et al. (Scientific Reports)
Abstract The resurgence of COVID-19 and the rise in severe outcomes emphasize the need for reliable prognostic markers to guide patient care and optimize ICU and hospital resources. This study investigates the potential of nasopharyngeal swabs to identify biomarkers that predict ICU admission or death in hospitalized COVID-19 patients. We analyzed nasopharyngeal exudates from 95 hospitalized patients in 2020 using high-plex RNA quantification on the NanoString® nCounter platform. Comparative analysis identified four genes, with KLRB1 (Killer cell lectin like receptor B1) (Odds Ratio OR 0.5, 95% CI: 0.27–0.96), along with age (OR 3.3, 95% CI: 1.25–8.93) emerging as independent prognostic markers in multivariate analysis. These findings were validated using qRT-PCR in an independent cohort of 168 patients hospitalized in 2022. While univariate analysis identified a significant association between KLRB1 expression and vaccination status (p < 0.05), only low KLRB1 expression (OR 1.135, 95% CI: 1.0-1.280), and age (OR 1.033, 95% CI: 1.006–1.061) were confirmed as independent risk factors for ICU admission or death, regardless of other studied variables such as comorbidities, vaccination status, or smoking habits. Our findings suggest that KLRB1 expression could improve prognostic tools by identifying patients at higher risk upon admission. Incorporating KLRB1 into multiplex diagnostic kits alongside SARS-CoV-2 detection could streamline prognostic assessment, providing a more comprehensive and efficient approach to patient management.